Efektivitas Pemberian Video Health Education Dan Leaflet Terhadap Pengetahuan Ibu Hamil Tentang Personal Hygiene - Wahyuni, Nur Ismi; SR, Nurqalbi (Madu : Jurnal Kesehatan, 2023)
Pregnancy is a process that involves various hormones in the body. Personal hygiene in pregnant women is influenced by several factors, one of which is knowledge. Knowledge of personal hygiene for pregnant women is very important because good knowledge can improve the health of pregnant women themselves. This research aims to determine the effectiveness of providing health education videos and leaflets on pregnant women's knowledge about personal hygiene. The type of research used is experimental research with the experimental method used, namely Quasi Experimental, with a "Two group Pretest Posttest" design, with independent T-Test statistical tests. The population in this study were all pregnant women at the Al-Ikhlas clinic. The sampling technique was purposive sampling, the sample size was 30 people. Based on the results of the T-Independent Test, the effectiveness of health education about personal hygiene using video media and leaflets on the knowledge of pregnant women shows that the p value is 0.007, so it shows that the results of Ho are rejected and Ha is accepted, which means that there is a difference in health education about personal hygiene using video media and leaflet on knowledge of pregnant women